DISTINCTION OF PLATINUM GROUP ELEMENTS (PGE) GEOCHEMISTRY BETWEEN THE JINBAOSHAN AND BAIMAZHAI MAGMATIC SULFIDE DEPOSITS IN YUNNAN PROVINCE, CHINA, AND ITS IMPLICATION FOR ORE GENESIS - Wang S.; Sun X.; Shi G.; Xiong D.; Zai W. (My University, 2007)
The Jinbaoshan and Baimazhai ore deposits are two magmatic sulfide deposits hosted in the Emeishan large igneous provinces. In this paper, platinum group elements (PGE) geochemistry of the two deposits were compared, and the results show that the Jinbaoshan is characterized by high total PGE (∑PGE), low (Cu+ Ni), Pd/Ir (3.84-26.49), Cu/Pd (46.91-1309.58) and Au/Pd ratios. On the contrary, the Baimazhai is characterized by low ∑PGE, high (Cu+Ni), Pd/Ir (4.72-297.2), Cu/Pd (10875.13-974788.55) and Au/Pd ratios. The two deposits have enantiomorphous primitive mantle normalized PGE patterns. The Jinbaoshan mine has more obvious positive correlation among PGE elements and Cu, Ni than the Baimazhai, probably implying that the PGE compositions in the Baimazhai intrusive was disturbed as its parent magma had experienced more complicated evolutional processes than the Jinbaoshan. Based on analytical data of this study and Yangliuping Cu-Ni-PGE deposit, the Cu-Ni-PGE ore formation processes of the Emei mantle plume are divided into three stages: 1) the Jinbaoshan stage, namely low S-saturation stage, during which the Emei mantle plume was mixed with a little crust material and just changed into S-saturated from unsaturated at the beginning of ascending, that a little sulfide melt segregated from silicate. Because of high patition coefficient of PGE between sulfide and silicate melt, a little sulfide melt can scavenge a large number of PGE from silicate melt. Consequently, the Jinbaoshan independent Pt-Pd deposit was formed by cumulation of a little PGE-enriched sulfide and the co-crystallizing olivine, pyroxene, chromite, etc. at high temprature; 2) the Yangliuping stage, or moderate S-saturated stage, during which the continuously ascending Emei mantle plume absorbed more crustal material and became moderately S-saturated and resulted in more PGE, Cu and Ni segretated from the silicate. More PGE, Cu and Ni accumulated and formed the Yangliuping deposit. 3) the Baimazhai stage, or high S-saturated stage, within which the terminal Emei mantle plume absorbed a lot of crustal material and became highly S-saturated, resulting in strong sulfide segregation. Cu, Ni and PGE in the silicate segregated with sulfide melt and formed independent Cu-Ni deposit.
Keywords: BAIMAZHAI; CU-NI-PGE SULFIDE DEPOSITS; EMEISHAN BASALT; JINBAOSHAN; PLATINUM GROUP ELEMENTS; YANGLIUPING